The use of pre-operative virtual reality to reduce anxiety in women undergoing gynecological surgeries: a prospective cohort study - Jason Ju In Chan; Cheng Teng Yeam; Hwei Min Kee; Chin Wen Tan; Rehena Sultana; Alex Tiong Heng Sia; Ban Leong Sng (BMC Anesthesiology, 2020)
Abstract Background Pre-operative anxiety is common and is associated with negative surgical outcomes. Virtual reality (VR) is a promising new technology that offers opportunities to modulate patient experience and cognition and has been shown to be associated with lower levels of anxiety. In this study, we investigated changes in pre-operative anxiety levels before and after using VR in patients undergoing minor gynecological surgery. Methods Patients who underwent elective minor gynecological surgeries in KK Women’s and Children’s hospital, Singapore were recruited. The VR intervention consisted of 10-min exposure via a headset loaded with sceneries, background meditation music and breathing exercises. For the primary outcome of pre-operative anxiety, patients were assessed at pre- and post-intervention using the Hospital Anxiety and Depression Scale (HADS). Secondary outcomes of self-reported satisfaction scores and EuroQol 5-dimension 3-level (EQ-5D-3L) were also collected. Results Data analysis from 108 patients revealed that HADS anxiety scores were significantly reduced from 7.2 ± 3.3 pre-intervention to 4.6 ± 3.0 post-intervention (p < 0.0001). Furthermore, HADS depression scores were significantly reduced from 4.7 ± 3.3 pre-intervention to 2.9 ± 2.5 post-intervention (p < 0.0001). Eighty-two percent of the patients self-reported VR intervention as ‘Good’ or ‘Excellent’. EQ-5D-3L showed significant changes in dimensions of ‘usual activities’ (p = 0.025), ‘pain/discomfort’ (p = 0.008) and ‘anxiety/ depression’ (p < 0.0001). Conclusions For patients undergoing minor gynecological procedures, the VR intervention brought about a significant reduction in pre-operative anxiety. This finding may be clinically important to benefit patients with high pre-operative anxiety without the use of anxiolytics. Trial registration This study was registered on clinicaltrials.gov registry ( NCT03685422 ) on 26 Sep 2018.